Simulation of lateral transshipment in order delivery under e-commerce environment. (2016) - Liu, Haibin
In this research, we apply a discrete event simulation approach to explore how enterprises in the Chinese mainland make a successful operation with the aid of e-commerce. This paper examines the effects of proposed four kinds of transshipment operation network structures on the performance under different policies of transshipment and inventory allocation. Results show that: 1) transshipment based on availability (TBA) policy can produce the high service level, while transshipment based on the inventory equalisation (TIE) policy can give high profits; 2) adoption of TBA or TIE is contingent on different stages of development; 3) an optimal service level and performance can both be acquired at the same time by adjusting transshipping structure; 4) the 'complete link' transshipping structure is the best in improving the service level; 5) the 'small-world' transshipping structure is optimal; 6) the 'scale-free' transshipping structure should be averted forming in operation.